Shwachman-Diamond syndrome and type 1 diabetes mellitus: more than a chance association? - Gana, S; Sainati, L; Frau, M R; Monciotti, C; Poli, F; Cannioto, Z; Comelli, M; Danesino, C; Minelli, A (Exp Clin Endocrinol Diabetes, 2011)
Shwachman-Diamond syndrome is a rare clinical condition consisting of exocrine pancreatic dysfunction, various degree of pancytopenia, and metaphyseal dysplasia. The majority of Shwachman-Diamond syndrome cases result from mutations in the Shwachman-Bodian-Diamond Syndrome gene. To date, type 1 diabetes mellitus has only been reported in 4 independent cases presenting with Shwachman-Diamond syndrome, 3 of them with molecular confirmation of the diagnosis. We describe 2 unrelated patients with clinical and molecular features typical of Shwachman-Diamond syndrome and type 1 diabetes mellitus. In addition, we report the occurrence rate of type 1 diabetes mellitus in the Italian registry for Shwachman-Diamond syndrome, which is low (3.23%) but increased at least 30-fold over the type 1 diabetes mellitus occurrence rate in the general population. No evidence of a direct correlation between Shwachman-Diamond syndrome and type 1 diabetes mellitus have been reported, therefore the presence of both diseases in the same patient might be a chance association, however we suggest that the defects in immune regulation of Shwachman-Diamond syndrome might play a role in the development of type 1 diabetes mellitus.
Keywords: Bone Marrow Diseases; CD4-CD8 Ratio; Diabetes Mellitus, Type 1; Exocrine Pancreatic Insufficiency; Female; Heterozygote; Humans; Immune System; Infant; Italy; Lipomatosis; Male; Mutation; Prevalence; Proteins; Registries